The Effect of Talent Management And Teamwork With Mediation Performance Against Employee Job Satisfaction In Rectorate Universitas Negeri Padang (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
This study aims to Determine the effect of talent management and teamwork by mediating job satisfaction on employee performance in the Rectorate of Universitas Negeri Padang. This research is explanatory with quantitative methods. The sampling technique used in this study was purposive sampling for employees at the Rectorate Universitas Negeri Padang with a sample of 116 respondents. This research uses Partial Least Square with SmartPLS 3.0 program. The results showed that talent management and significantly affects positively on employee performance, then teamwork and Significant influences positively on employee performance, talent management and significant positively influences on job satisfaction, then teamwork and significant positively influences on job satisfaction, and job satisfaction positively and significant affects on employee performance, then talent management and teamwork also affect performance with employee job satisfaction, as a mediating variable. The implication of this study is to improve talent management and teamwork to improve employee performance by mediating job satisfaction on employee performance in the Rectorate of Universitas Negeri Padang.